Magnetic hydrogel bead, preparation method thereof and application of magnetic hydrogel bead in polycyclic aromatic hydrocarbon detection
Through the preparation and application of NiFe2O4@MXene@CS magnetic hydrocarbon beads, combined with HPLC-FLD technology, the problem of PAH detection in food was solved, and efficient and environmentally friendly PAH adsorption and detection effects were achieved.
Patent Information
- Application Number
- CN202411320232.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to detect the widespread and low content of polycyclic aromatic hydrocarbons in food efficiently, easily and environmentally friendly, and traditional extraction methods have problems such as poor environmental friendliness and cumbersome operation.
The preparation method of NiFe2O4@MXene@CS magnetic hydrogreasing beads was adopted to synthesize NiFe2O4@MXene composite material by co-precipitation method and modify it into magnetic hydrogreasing beads. Combined with HPLC-FLD technology, it can achieve efficient adsorption of polycyclic aromatic hydrocarbons. and detection.
It realizes highly selective adsorption and detection of polycyclic aromatic hydrocarbons in complex samples, simplifies the extraction process, reduces costs, and is environmentally friendly and efficient, and is suitable for the detection of polycyclic aromatic hydrocarbons in food.
Smart Images

Figure CN119386823A_ABST
Abstract
Description
Technical Field
[0003] The present invention relates to the technical field of hydrogel materials, in particular to a magnetic hydrogel bead and a preparation method thereof and application thereof in the detection of polycyclic aromatic hydrocarbons. Background Art
[0004] Polycyclic aromatic hydrocarbons (PAHs) are a class of persistent organic pollutants (POPs) consisting of two or more benzene rings that are ubiquitous in the environment. PAHs are widely present in the environment and food and are toxic, teratogenic, and carcinogenic. Upon ingestion, their metabolites bind to macromolecules such as proteins and DNA, causing damage to the body. Dietary intake is one of the primary pathways of human exposure to PAHs, influenced by pre-existing food contaminants (in air, water, and soil) and their formation and accumulation during food processing. my country's National Food Safety Standard for Contaminants in Food (GB 2762-2017) stipulates limits for benzo[a]pyrene in four food categories: <5.0 μg / kg for benzo[a]pyrene in cereals and their products, meat and meat products, and aquatic animals and their products, and <10 μg / kg for benzo[a]pyrene in oils and fats and their products. PAHs contamination is widespread, but PAHs are generally present at very low levels and in a wide variety of forms, typically at the ppb or even ppt level. Currently, there is no single method that can directly detect all PAHs. Furthermore, food contains a complex matrix, which presents significant difficulties in extracting PAHs, leading to significant errors in the final test results. Detecting PAHs in food is challenging.
[0005] The traditional extraction method for PAHs is Soxhlet extraction, but this method has drawbacks such as high organic solvent usage, poor environmental friendliness, and a cumbersome operation. Therefore, it is often used as a reference to evaluate the extraction effectiveness of other methods. In recent years, with the increasing breadth and depth of PAH research, sample pretreatment techniques have also been continuously improved, such as dispersive liquid-liquid extraction, solid-phase extraction, and solid-phase microextraction. Finding a simple, efficient, and environmentally friendly PAH detection method would significantly reduce costs and be of great value in food contaminant detection. Summary of the Invention
[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a magnetic hydrogel bead and a preparation method thereof and an application thereof in the detection of polycyclic aromatic hydrocarbons. The technical solution adopted by the present invention is as follows:
[0007] In a first aspect, a method for preparing magnetic hydrogel beads is provided, comprising the following steps:
[0008] S1. Synthesis of NiFe2O4@MXene: NiCl2·6H2O and FeSO4·7H2O were dissolved in pure water to obtain a mixture, and the pH of the mixture was adjusted to 11 with NaOH solution. Ti3C2 MXene was added to the mixture, mixed thoroughly, and heated in a water bath with continuous stirring for a period of time. The solid product was then collected by centrifugation, washed, and dried to obtain NiFe2O4@MXene.
[0009] S2. Preparation of NiFe2O4@MXene@Cs magnetic hydrogel beads: Chitosan was added to acetic acid and pure water to obtain a mixture. After magnetic stirring overnight, NiFe2O4@MXene was added. The mixture was sonicated and refrigerated for a period of time. It was then placed in a mold to prepare magnetic beads. NaOH solution was then added dropwise under continuous magnetic stirring. The obtained magnetic beads were immersed in the NaOH solution for a period of time and then washed with ultrapure water several times. The prepared magnetic hydrogel beads NiFe2O4@MXene@Cs were dispersed in glutaraldehyde solution and stirred. Finally, the rinsed magnetic hydrogel beads were dispersed in water for later use.
[0010] The preparation method of Ti3C2 MXene in step S1 includes: adding LiF to HCl and magnetically stirring until it is completely dissolved, then slowly adding Ti3AlC2 thereto, mixing and stirring at room temperature in a fume hood for a period of time, washing and centrifuging until the pH value of the eluate is 5.5-6.5, and finally drying in a vacuum drying oven to obtain Ti3C2 MXene material.
[0011] In a second aspect, magnetic hydrogel beads prepared by the above-mentioned method for preparing magnetic hydrogel beads are provided.
[0012] In a third aspect, the present invention provides an application of the magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons, in particular, an application of the magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons in food.
[0013] Preferably, the application steps include: placing the magnetic hydrogel beads into a container containing the sample solution to be tested, and then placing it in a constant temperature oscillation device for a certain period of time to allow the magnetic hydrogel beads to oscillate evenly in the solution. After the oscillation is completed, a magnet is placed on the outer wall of the container to separate the magnetic hydrogel beads from the aqueous phase; the magnetic hydrogel beads are eluted with toluene, the resulting eluate is transferred to a centrifuge tube, dried with nitrogen, re-dissolved with acetonitrile, and then analyzed using HPLC-FLD (high performance liquid chromatography-fluorescence detection).
[0014] As a preference, in the application, NiFe2O4@MXene@CS with hydrogel beads of 5 mm is selected.
[0015] Preferably, in the application, the vibration time in the constant temperature oscillation device is 25-40 minutes.
[0016] Preferably, in the application, the salt concentration of the sample solution to be tested is maintained at 0%-2%; most preferably, in the application, the salt concentration of the sample solution to be tested is maintained at 0.95-1.05%.
[0017] The beneficial effects of the present invention are as follows: the present invention provides a preparation method of NiFe2O4@MXene@CS magnetic hydrogel beads, and establishes a microextraction technology based on the preparation method of NiFe2O4@MXene@CS (NMCs) magnetic hydrogel beads; by modifying the physicochemical structures of chitosan and MXene, a high degree of selectivity for polycyclic aromatic hydrocarbons in complex samples is achieved, and the density of adsorption sites is increased by adding new functional groups; at the same time, the chitosan powder is modified into hydrogel beads, which not only retains high reaction sites but also plays an intercalation role to realize the exfoliation of layered MXene materials, obtain a larger specific surface area, reduce MXene oxidation and agglomeration, and improve the adsorption selectivity of target analytes, providing a new detection idea for the detection of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments, test examples, application examples or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still fall within the scope of the present invention.
[0019] Figure 1 In the figure, AD are SEM images, where: A is NiFe2O4; B is MXene; C is NiFe2O4@MXene; D is NiFe2O4@MXene@Cs; EH are TEM images, where: E is NiFe2O4; F is MXene; G is NiFe2O4@MXene; H is NiFe2O4@MXene@Cs; Figure 2 XRD characterization of each material in the examples;
[0020] Figure 3 FT-IR diagram of each material in the embodiment
[0021] Figure 4 The hysteresis loop characterization of NMCs in the embodiment;
[0022] Figure 5 This is a diagram showing the adsorption effects of hydrogel beads of different materials and sizes on five PAHs;
[0023] Figure 6 The target extraction efficiency diagram at different pH (the different color columns represent the substances and Figure 5 same);
[0024] Figure 7 The extraction efficiency diagram of five PAHs at different extraction times;
[0025] Figure 8 The figure shows the extraction efficiency of five PAHs in samples with different salt concentrations;
[0026] Figure 9 The effect of different magnetic hydrogel particles on the extraction efficiency in the same volume of sample solution;
[0027] Figure 10 is the extraction efficiency after repeated elution of magnetic hydrogel beads with toluene for several times;
[0028] Figure 11 Chromatogram of the sample detected by NMCs-HPLC-FLD method under optimal conditions;
[0029] Figure 12 Adsorption capacity changes of NiFe2O4@MXene@Cs for five PAHs. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to embodiments, test examples, application examples and accompanying drawings.
[0031] 1. Experimental reagents and instruments
[0032] The experimental reagents used in the present invention include: fluorene (Flu), anthracene (Ant), CHR, pyrene (Pyr), and benzo[a]pyrene (BaP) (purity >98.0%) were purchased from Aladdin Reagents (Shanghai, China) as representative PAH species. Titanium aluminum carbide (Ti3AlC2) and chitosan (CS) were purchased from MacLean Co., Ltd. (China). Sodium hydroxide, glutaraldehyde, acetic acid, hydrochloric acid, and ethanol were purchased from Sinopharm Chemical Reagent Co., Ltd. (Beijing, China). Chromatographic-grade methanol and acetonitrile were purchased from J&K Technologies (Shanghai, China) for washing. Polyethersulfone (PES) and nylon (NL) filter membranes with pore sizes of 0.22 μm and 0.45 μm, respectively, were purchased from Shanghai Anpu Scientific Instrument Co., Ltd. for filtration. Ultrapure water (18.2 MΩ, 25°C) (Millipore Mill-Q Plus System, Bedford, MA, USA) was used to prepare sample solutions and mobile phase.
[0033] The experimental instruments used in the present invention include: a BS210S electronic balance (Sartorius, Germany); an XH-D vortex mixer (Shanghai Zhengqiao Instrument Co., Ltd.); an HJ-6A magnetic stirrer (Jintan, Jiangsu, China); a TDL-50C low-speed centrifuge (Anting Instrument Factory, Shanghai, China); an HC-3518 high-speed centrifuge (USTC Zonkia, Hefei, Anhui); a DZF-6090 vacuum dryer (Ziyi, Shanghai, China); a DHG-9123 electric constant temperature blast drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd., Shanghai, China); a PB-10 pH meter (Sartorius, Germany); and an Agilent-1260 high performance liquid chromatograph (USA) equipped with a fluorescence detector (FLD).
[0034] 2. Standard Solution and Sample Preparation
[0035] Five PAHs were dissolved in 50 mL of methanol to prepare 100 mg·L -1 Standard solution. Then, the standard solution was diluted with an appropriate volume of methanol to prepare a working standard solution (Flu is 10 mg·L -1 , Ant, Chr and Pyr were 5 mg·L -1 , BaP is 2.5 mg·L -1 ) and stored in a refrigerator at 4°C for later use. Fresh apples, oranges, coconuts and various types of pure milk (including skimmed, semi-skimmed, and high-fat) were purchased from the supermarket. Among them, the three fruits were juiced and filtered with a 0.45μm organic membrane and stored in the refrigerator. The milk was simply processed: 5mL of milk was added to 1mL of 10% acetic acid, made up to volume with ultrapure water, vortexed for 5min, ultrasonicated for 30min, heated in a 90°C water bath for 40min, and then centrifuged for 40min at 4000rpm. The milk supernatant was taken for subsequent analysis.
[0036] 3. Chromatographic conditions
[0037] To detect PAHs in samples, an Agilent -1 Qualitative and quantitative analysis was performed using a 260 HPLC system. PAHs were separated using an Eclipse XDB-C18 column (5 μm, 4.6 × 150 mm) with a binary mobile phase of acetonitrile (A) and water (C). The sample injection volume was 5 μL at a flow rate of 1.0 ml min -1Samples were measured at a constant flow rate of 100 nm and a constant column temperature of 30°C. The mobile phase gradient was as follows: 65% to 73% A from 0 to 12.0 min; 73% to 100% A from 12.0 to 17.0 min. The detection wavelengths of the FLD were set as follows: (1) Ex / Em: 260 / 336 nm at 6.0 min; (2) Ex / Em: 250 / 380 nm at 7.5 min; (3) Ex / Em: 270 / 385 nm at 9.0 min; and (4) Ex / Em: 260 / 420 nm at 15 min.
[0038] Example
[0039] 1. Synthesis of MXene
[0040] Weigh 2.4 g of LiF and add it to 35 mL of 9 mol·L -1 HCl, magnetic stirring 5 -1 0 min until completely dissolved, then 1.5 g of Ti3AlC2 was slowly added thereto, mixed and stirred at room temperature in a fume hood for 24 h, washed the material with ultrapure water 3-5 times, and centrifuged 3-5 times until the pH value of the eluate was around 6. Finally, it was placed in a vacuum drying oven at 60 ° C for 6 h to obtain MXene material.
[0041] 2. Synthesis of NiFe2O4@MXene
[0042] 1 mol·L was prepared by using 4 g NaOH and 100 mL ultrapure water. -1 Weigh 0.252g of NiCl2·6H2O and 0.576g of FeSO4·7H2O and mix with 80mL of ultrapure water. Adjust the pH to 11 with the prepared NaOH solution. Add 1g of Ti3C2 MXene to the mixture, stir magnetically for 30 minutes, and then continue stirring in an 80°C water bath for 3 hours. Collect the solid product by centrifugation at 8000 rpm for 3 minutes, wash it three times with ultrapure water and ethanol, and finally dry it in a vacuum oven at 60°C for 4 hours to obtain NiFe2O4@MXene solid powder.
[0043] 3. Preparation of NiFe2O4@MXene@Cs magnetic hydrogel beads
[0044] First, 0.75g chitosan was weighed and added to a mixture of 1.26mL acetic acid and 23.74mL ultrapure water. After magnetic stirring overnight, 0.2g NiFe2O4@MXene was added. The mixture was ultrasonicated and refrigerated for 30min, and then placed in a mold to prepare magnetic beads. Then, 2.5mol·L -1The obtained magnetic beads were immersed in the NaOH solution for 30 min in turn. After washing with ultrapure water for several times, the prepared magnetic hydrogel beads (NMCs) were dispersed in 100 mL of glutaraldehyde solution (1 wt%) and stirred for 2 h. Finally, the rinsed magnetic hydrogel beads were dispersed in water for later use.
[0045] 4. NMCs-HPLC-FLD Method Procedure
[0046] Place the magnetic hydrogel beads into a centrifuge tube containing 30 mL of PAH solution and add 0.1 mol·L -1 HNO3 and 0.1 mol·L -1 The pH value of the mixture was adjusted with NaOH, and then the mixture was placed in a constant temperature oscillation device and vibrated for a certain period of time to allow the magnetic hydrogel beads to oscillate evenly in the solution. After the oscillation is completed, the adsorption reaction is completed. Subsequently, a magnet was placed on the outer wall of the test tube to separate the magnetic hydrogel beads from the aqueous phase. The magnetic hydrogel beads were eluted twice with 500 μL of toluene, and the eluates obtained twice were transferred to a 2.0 mL centrifuge tube, dried with nitrogen, re-dissolved with 300 μL of acetonitrile, and analyzed using HPLC-FLD.
[0047] Test Example 1 Material Characterization
[0048] 1. SEM and TEM
[0049] SEM and TEM are used to characterize the surface and transmission morphology of nanomaterials. Figure 1 As shown in Figures A-H, an ordered multilayer morphology can be observed in the NiFe2O4@MXene composite material, with a large number of NiFe2O4 nanoparticles uniformly deposited on the MXene surface or inserted into the interlayer of the MXene. After modification with NiFe2O4, the original accordion-shaped MXene surface becomes rougher, which is more conducive to the adsorption of polycyclic aromatic hydrocarbons. The SEM and TEM images of NMCs are shown in Figures A-H, respectively. Figure 1 As shown in Figures D and 1H, compared with the images of NiFe2O4@MXene, the addition of CS results in an obvious honeycomb layered structure and an increase in specific surface area.
[0050] 2.XRD analysis
[0051] Figure 2The XRD spectrum shows that the representative peaks of MXene are at 8.8 and 18.1. The presence of characteristic MXene peaks in the NMCs composite material indicates that the two-dimensional structure of MXene is successfully formed in the composite. However, the peak heights are significantly different, which may be due to the change in the atomic species of the material after the incorporation of MXene, resulting in a decrease in peak intensity. Characteristic diffraction peaks of NiFe2O4 appear at 35.7°, 43.4°, 63.0°, and 74.6° 2θ, which are attributed to the (311), (400), (440), and (533) crystal planes of NiFe2O4, respectively, indicating that the synthesized product is a spinel structure NiFe2O4@MXene@Cs. The main diffraction peaks of the product are sharp, indicating its good crystallinity; no obvious miscellaneous peaks appear.
[0052] 3. FTIR analysis
[0053] The materials NiFe2O4, MXene, CS, NiFe2O4@MXene@CS and NiFe2O4@MXene@CS+PAHs were analyzed by Fourier transform infrared spectroscopy ( Figure 3 As shown). It can be seen that the infrared spectrum of NiFe2O4@MXene@CS has the same absorption peak as MXene, indicating that the vibration of the chemical bonds and functional groups of the two in the infrared spectrum is similar, and MXene has been modified onto the NMC surface. 607cm -1 The peaks at 1630 and 1098 cm are caused by Fe-O stretching vibration, which indicates that NiFe2O4 is successfully attached to NMCs. -1 The absorption peaks are the vibration peaks of C=C and COC; 3450 and 3141 cm -1 The broad absorption peaks at 1630 cm-1 are the free water peak and the associated OH stretching vibration. After extraction, the C=C bond stretching vibration of the benzene ring in PAHs may cause -1 A peak appears.
[0054] 4. Hysteresis loop
[0055] The magnetic curves of each material were measured at room temperature by a vibrating sample magnetometer (VSM). Figure 4As shown. All samples showed typical S-type MH curves, indicating the presence of ferromagnetism. The saturation magnetization (Mmax), residual magnetization (Mr) and coercive field (Hc) of NMCs were 8.18emu / g, 0.31emu / g and 34.3Oe, respectively, while after extraction they decreased to 2.63emu / g, 0.17emu / g and 21.7Oe, respectively. The slight decrease in Mmax after extraction may be due to the fact that the adsorbed PAHs formed a covering layer on the surface of the material, thereby affecting the magnetization. Although the magnetization of the composite material prepared by the present invention is reduced after further modification, it can still quickly achieve the adsorption of polycyclic aromatic hydrocarbons.
[0056] Application Example 1 Optimal Conditions for NMCs-HPLC-FLD Program
[0057] 1. Selection of magnetic hydrogel beads
[0058] First, the adsorption efficiency of five types of hydrogel beads, namely NiFe2O4@MXene@Cs (3mm diameter); NiFe2O4@MXene@Cs (5mm diameter); MXene (5mm diameter); NiFe2O4 (5mm diameter); and Cs (5mm diameter) were studied. NiFe2O4 has good magnetic separation performance and chemical stability, and the material itself has a variable structure and adjustable properties. MXene has good hydrophilicity, biocompatibility, environmental friendliness, conductivity, catalytic properties, and a large specific surface area with more reaction sites, which makes it have good application prospects in the field of adsorption treatment of organic and inorganic pollutants such as dyes and metal ions. Figure 5 As shown, NiFe2O4@MXene@Cs (diameter 5 mm) has the best adsorption effect, so NMCs with hydrogel beads of 5 mm are preferred.
[0059] 2. Selection of solution pH
[0060] Each substance has its own specific pKa value. The pH value can affect the surface charge between the adsorbate and the adsorbent. The mechanism is protonation and deprotonation, that is, the surface charge can cause repulsion or attraction between the adsorbate and the adsorbent. Therefore, the pH value of the solution will affect the extraction effect to a certain extent (such as Figure 6 The optimal pH conditions were studied within the pH range of 3 to 11. The results showed that the increase in pH did not significantly affect the extraction efficiency of the target compound. Therefore, the pH is generally not adjusted during application of the present invention.
[0061] 3. Selection of extraction time
[0062] Time has an important influence on the reaction rate, extraction efficiency, equilibrium state, etc. in the extraction reaction. Therefore, it is necessary to determine the optimal reaction time according to the specific situation. The experiment examined the effect of the extraction effect within 10 minutes to 50 minutes by changing the shaking time. The results are as follows Figure 7 As shown, the extraction efficiency increases with increasing shaking time, reaching equilibrium at 30 minutes. After 30 minutes, the extraction efficiency decreases. This may be related to excessive extraction of solutes when the extraction time is too long, resulting in increased impurities in the extract and reduced purity. Therefore, considering the combined sensitivity of the test method and analytical efficiency, a shaking time of 30 minutes is preferred.
[0063] 4. Selection of salt concentration
[0064] The ionic strength of the solution will lead to different competitive adsorption in the system, so the mass fraction of NaCl will affect the extraction recovery rate. Figure 8 As shown in the figure, when the NaCl concentration increases from 0% to 1%, the extraction efficiency increases rapidly. However, when the NaCl concentration increases from 1% to 11%, the extraction efficiency gradually decreases and stabilizes after 5%. Therefore, the extraction effect is best when the salt concentration is 1%.
[0065] 5. Selection of hydrogel particles
[0066] The number of adsorbent particles will affect the total adsorption capacity of the adsorbent. Generally speaking, more adsorbent particles means a larger surface area and adsorption sites, which can adsorb more target substances and improve the extraction efficiency. Figure 9 In a 30mL water sample, the extraction efficiency increased rapidly and reached its optimum when the number of hydrogel beads increased from 1 to 3. However, the extraction efficiency decreased when the number of hydrogel beads increased from 3 to 5. This is likely due to the large number of beads, which caused collisions between the beads and reprecipitated the target compound. Therefore, the optimal number of hydrogel beads for a 30mL water sample was 3.
[0067] 6. Reusability of magnetic hydrogel beads
[0068] To evaluate the number of times the magnetic hydrogel beads can be used, repeated adsorption-desorption experiments were performed on PAHs in water samples using the beads. Three beads were dispersed in 30 mL of water sample, shaken for 30 minutes, and eluted with toluene. After repeating the above operation six times, the recovery rate of PAHs in water samples with the magnetic hydrogel beads was RSD < 8.3%, and the ERs decreased by approximately 19.3% ( Figure 11 ), indicating that the magnetic hydrogel beads have good reusability and reduce the cost of the method.
[0069] Application Example 2 Performance Analysis of NMCs-HPLC-FLD Method
[0070] In this application example, a series of indicators were used to evaluate the analytical performance of the newly developed NMCs-HPLC-FLD microextraction technique. The results are shown in Table 1. 2 values (0.9924-0.9998) and wide LRs (0.07-0.27-200 μg·kg -1 ), good stability and wide application range, LOD is 0.02-0.08μg·kg -1 The LOQ is between 0.07 and 0.27 μg·kg -1 In addition, we also tested the three concentration levels of low, medium and high (low = 2 μg·kg -1 , medium = 50 μg·kg -1 Hehe = 100 μg·kg -1 ) to assess experimental precision. The same batch of samples was tested six times, with injections every two hours, to determine intra-day precision. The same samples were tested daily at 8:00 AM for six consecutive days to determine inter-day precision. The resulting intra-day and inter-day RSDs were 2.6-5.7% and 2.9-6.9%, respectively, demonstrating excellent repeatability and reproducibility of the NMCs-HPLC-FLD method.
[0071] Table 1 Analytical performance of the NMCs-HPLC-FLD method
[0072]
[0073] Note: (1) “Low” indicates 2μg·kg -1 ; "Medium" indicates 50μg·kg -1 ; "High" indicates 100μg·kg -1
[0074] Application Example 3: Analysis of actual samples
[0075] Under the optimal conditions formed by combining the various preferred conditions screened in Application Example 1, the newly developed NMCs-HPLC-FLD method was used to detect PAHs in juice and milk samples, including apple juice, orange juice, coconut water, and skim, semi-skim, and high-fat milk samples. As shown in Tables 2 and 3, the five PAHs detected in multiple samples ranged from 0.10 -1 .53μg·kg -1The presence of PAHs in juice or milk may be caused by pollution from soil contamination, rainfall, and other processes in the environment, as well as the generation or introduction of PAHs during production, processing, and transportation. PAH concentrations should be strictly monitored and extensively investigated for future risk assessment, restrictions, and dietary guidance. All samples were spiked at three levels (2 μg·kg -1 , 50 μg·kg -1 and 100 μg·kg -1 ), the recovery rates (ER) of the five PAHs ranged from 70.3% to 108.6%. Figure 11 The liquid chromatogram in Figure 2 shows that the NMCs-HPLC-FLD method reduces the interference of impurities in the sample. In summary, the newly developed method can effectively achieve the pre-enrichment and determination of trace PAHs in juice and milk samples.
[0076] Table 2 Recovery and relative standard deviation of spiked juice
[0077]
[0078] Table 3 Recovery and relative standard deviation of spiked milk
[0079]
[0080] Comparative Example
[0081] The present inventors evaluated the analytical performance of the newly developed NMCs-HPLC-FLD method for the detection of PAHs in milk and juice samples. As shown in Table 4, the detection limit of the NMCs-HPLC-FLD method (0.02-0.08 μg kg -1 ) is lower than similar studies in the prior art for the enrichment of PAHs, such as DESs-HPLC-FLD (0.03-0.3 μg kg -1 ), SFC-QqQ-MS (0.04-0.24μg·kg -1 ), LLE-HPLC-FLD (0.03-1.66μg·kg -1 ) and IL-HF-LPME / HPLC-DAD (0.14-0.71 μg·kg -1 , more than 10 times lower) and STL-GC-FID for the detection of juice samples (8.47-55.96 μg·kg -1 , more than 400 times lower).
[0082] Compared with other microextraction methods in the prior art, the newly developed NMCs-HPLC-FLD method has several advantages. First, this method is simple to operate and does not require weighing the extractant. Second, compared with traditional volatile solvents, magnetic hydrogel beads are more stable, environmentally friendly, and easy to carry and store. Third, phase separation is achieved through rapid magnetic separation (only a few seconds), which saves at least 5 seconds of time. -1 The method eliminates the need for a tedious centrifugation step (0-min), thus shortening the overall microextraction process. Fourthly, the method does not require specialized extraction equipment, such as solid-phase extraction cartridges. Finally, it can still achieve low LODs and high ERs when processing complex juice and milk samples. In summary, compared with existing methods, the NMCs-HPLC-FLD method provided by the present invention is more efficient, economical, and environmentally friendly.
[0083] Table 4 Comparison of different methods
[0084]
[0085] Note: (1)DESs: deep eutectic solvents; (2)SFC: supercritical fluidchromatography; (3)STL: spent tea leaves; (4)IL-HF-LPME: hollow fiber supportedionic liquids liquid-phase micro-extraction method
[0086] Adsorption kinetics mainly describes the adsorption rate of the adsorbent and reflects the dynamic changes of adsorption. Figure 12 As shown in the figure, the adsorption capacity of NiFe204@MXene@Cs for the five PAHs increases rapidly from 0 to 60 min, and there is no significant change in the adsorption capacity after 60 min, indicating that the adsorption of the five target substances by NiFe204@MXene@Cs reaches equilibrium at 60 min. The maximum adsorption capacity (Qm) of NMCs for Flu, Phe, Chr, Pyr and BaP are 12.2, 25.5, 27.1, 29.5 and 22.2 mg·g, respectively. -1 The high adsorption capacity of NMCs (12.2-22.2 mg·g -1 ) and fast adsorption kinetics can be explained by the fact that the abundant amino groups on the surface of NMCs enable strong hydrogen bonding and π-π interactions between the nanocomposites and PAHs, thereby enhancing the adsorption affinity.
[0087] In summary, the present invention prepared uniform layered NiFe2O4@MXene@Cs (NMCs) adsorbent by co-precipitation method and established an analytical method for the detection of five PAHs in juice and milk samples by combining HPLC-FLD technology. The five PAHs were in the range of 0.07-0.27-200 μg·kg -1 The linear relationship was good within the range (r≥0.9924), and the detection limit was 0.02~0.08μg·kg -1 The recovery rate was 70.3% to 108.6%, and the intra-day and inter-day precision was ≤6.9%. When the sample volume was 30 mL, using 3 NiFe2O4@MXene@Cs magnetic hydrogel beads, it only took 30 minutes. After the adsorbent was reused 6 times, the ERs of polycyclic aromatic hydrocarbons decreased by about 19.3%, and the recovery rate RSD was ≤8.3%. In addition, the adsorbent can separate the analyte from the sample matrix by simply applying an external magnetic field, without the need for centrifugal filtration, and the operation is simple and convenient. In summary, this method is simple, efficient and rapid, enriching the application of two-dimensional material MXene in the field of pretreatment, and providing new ideas for the analysis of polycyclic aromatic hydrocarbons in complex samples.
[0088] The above disclosure is merely a preferred embodiment of the present invention and certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing magnetic hydrogel beads, characterized in that: The following steps are involved: S1. Synthesis of NiFe2O4@MXene: NiCl2·6H2O and FeSO4·7H2O were dissolved in pure water to obtain a mixture, and the pH value thereof was adjusted to 11 with NaOH solution. Ti3C2 MXene was added to the mixture, and the mixture was evenly mixed and heated in a water bath and stirred for a period of time. The solid product was then collected by centrifugation, and the solid product was washed and dried to obtain NiFe2O4@MXene. S2. Preparation of NiFe2O4@MXene@Cs magnetic hydrogel beads: chitosan was added to acetic acid and pure water to obtain a mixture. After magnetic stirring overnight, NiFe2O4@MXene was added. The mixture was sonicated and refrigerated for a period of time, and then put into a mold to prepare magnetic beads. NaOH solution was then dropped into it under continuous magnetic stirring. The obtained magnetic beads were immersed in the NaOH solution for a period of time, and then washed with ultrapure water for several times. The prepared magnetic hydrogel beads NiFe2O4@MXene@Cs were dispersed in glutaraldehyde solution and stirred. Finally, the rinsed magnetic hydrogel beads were dispersed in water for later use.
2. The method for preparing magnetic hydrogel beads according to claim 1, characterized in that: The preparation method of Ti3C2MXene in step S1 includes: adding LiF to HCl and magnetically stirring until it is completely dissolved, then slowly adding Ti3AlC2 thereto, mixing and stirring at room temperature in a fume hood for a period of time, washing and centrifuging until the pH value of the eluate is 5.5-6.5, and finally drying in a vacuum drying oven to obtain the Ti3C2MXene material.
3. Magnetic hydrogel beads prepared by the method for preparing magnetic hydrogel beads as claimed in claim 1 or 2.
4. Use of the magnetic hydrogel beads described in claim 3 in the detection of polycyclic aromatic hydrocarbons.
5. Use of the magnetic hydrogel beads described in claim 3 in detecting polycyclic aromatic hydrocarbons in food.
6. The use of magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons according to claim 4, characterized in that: The application steps include: placing the magnetic hydrogel beads in a container containing the sample solution to be tested, and then placing it in a constant temperature oscillation device to vibrate for a certain period of time to make the magnetic hydrogel beads oscillate evenly in the solution. After the oscillation is completed, a magnet is placed on the outer wall of the container to separate the magnetic hydrogel beads from the aqueous phase; the magnetic hydrogel beads are eluted with toluene, the obtained eluate is transferred to a centrifuge tube, dried with nitrogen, re-dissolved with acetonitrile, and then analyzed using HPLC-FLD.
7. The use of the magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons according to claim 6, characterized in that: In the application, NiFe2O4@MXene@CS with hydrogel beads of 5 mm was selected.
8. The use of magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons according to claim 6, characterized in that: In the application, the vibration time in the constant temperature oscillation device is 25-40 minutes.
9. The use of magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons according to claim 6, characterized in that: During application, the salt concentration in the sample solution to be tested is maintained at 0%-2%.
10. The use of magnetic hydrogel beads in the detection of polycyclic aromatic hydrocarbons according to claim 9, characterized in that: During application, the salt concentration of the sample solution to be tested is maintained at 0.95-1.05%.